Training on Making Mini Studios as A Product Promotion Medium at UKM Walidayna: Pelatihan Pembuatan Mini Studio Sebagai Media Promosi Produk pada UKM Walidayna - Dani Manesah; Muhammad Ali Mursid Alfathoni; Aji Purnomo (Yayasan Ahmar Cendekia Indonesia, 2022)
This community service activity aims to provide training to Small and Medium Enterprises Walidayna. Training provided on the creation of a mini studio. A mini studio is a container used to photograph products. The results of the product photos will be used as promotional media. Small and Medium Enterprises Walidayna experienced obstacles when they wanted to promote products that had been made. Obstacles occur in the lack of creativity in product packaging in order to become an attractive promotional medium. The method used in this service activity begins with lectures, giving tutorials, conducting practicums, discussions, and evaluating activities. As for the results obtained from this activity, Small and Medium Enterprises Walidayna has a mini studio made from simple materials. With the mini studio container, Walidayna's Small and Medium Enterprises can package products into attractive promotional media. All participants were very enthusiastic about participating in the training provided by the implementation team for community service activities. Abstrak Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan pelatihan kepada Usaha Kecil Menengah Walidayna. Pelatihan yang diberikan tentang pembuatan mini studio. Mini studio merupakan wadah yang digunakan untuk memotret produk. Hasil foto produk tersebut akan dijadikan media promosi. Usaha Kecil Menengah Walidayna mengalami hambatan ketika hendak mempromosikan produk yang sudah dibuat. Hambatan terjadi kurangnya kreatifitas dalam pengemasan produk agar menjadi media promosi yang menarik. Metode yang digunakan dalam kegiatan pengabdian ini diawali dengan ceramah, memberikan tutorial, melakukan praktikum, diskusi, dan evaluasi kegiatan. Adapun hasil yang didapat dari kegiatan ini, Usaha Kecil Menengah Walidayna memiliki mini studio yang dibuat dari bahan-bahan sederhana. Dengan wadah mini studio tersebut Usaha Kecil Menengah Walidayna dapat mengemas produk menjadi media promosi yang menarik. Seluruh peserta sangat antusias mengikuti pelatihan yang diberikan oleh tim pelaksana kegiatan pengabdian kepada masyarakat.